"Everybody in this room can understand": A qualitative exploration of peer support during residency training. Issue 2 (29th March 2022) - Jain, Aarti; Tabatabai, Ramin; Schreiber, Jacob; Vo, Anne; Riddell, Jeffrey
Abstract: Objectives: Though peer support groups are often utilized during residency training, the dynamics, content, and impact of social support offered through peer support are poorly understood. We explored trainee perceptions of the benefits, drawbacks, and optimal membership and facilitation of peer support groups. Methods: After engaging in a peer support program at an emergency medicine residency program, 15 residents and 4 group facilitators participated in four focus groups in 2018. Interview questions explored the dynamics of group interactions, types of support offered, and psychological impacts of participation. The authors conducted a reflexive thematic analysis of data, performing iterative coding and organization of interview transcripts. Results: Discussions with experienced senior residents and alumni normalized residents' workplace struggles and provided them with insights into the trajectory of their residency experiences. Vulnerable group dialogue was enhanced by the use of "insider" participants; however, residents acknowledged the potential contributions of mental health professionals. Though groups occasionally utilized maladaptive coping strategies and lacked actual solutions, they also enhanced residents' sense of belonging, willingness to share personal struggles, and ability to "reset" in the clinical environment. Conclusions: Participants offered insights into the benefits and drawbacks of peer support as well as optimal peer group composition and facilitation. Support groups may be more effective if they engage a complementary model of alumni and pre‐briefed psychologist facilitators, avoid fatalism, and aim to foster intimate connections among residents. These findings can inform the development of future initiatives aiming to create a safe space for trainees to discuss workplace stressors.